Gold nanoparticles-embedded ceria with enhanced antioxidant activities for treating inflammatory bowel disease - Li, Mingyi; Liu, Jia; Shi, Lin; Zhou, Cheng; Zou, Meizhen; Fu, Daan; Yuan, Ye; Yao, Chundong; Zhang, Lifang; Qin, Sumei; Liu, Miaodeng; Cheng, Qian; et al. (Bioactive materials, 2023)
The excessive reactive oxygen species (ROS) is a hallmark associated with the initiation and progression of inflammatory bowel disease (IBD), which execrably form a vicious cycle of ROS and inflammation to continually promote disease progression. Here, the gold nanoparticles-embedded ceria nanoparticles (Au/CeO2) with enhanced antioxidant activities are designed to block this cycle reaction for treating IBD by scavenging overproduced ROS. The Au/CeO2 with core-shell and porous structure exhibits significantly higher enzymatic catalytic activities compared with commercial ceria nanoparticles, likely due to the effective exposure of catalytic sites, higher content of Ce (III) and oxygen vacancy, and accelerated reduction from Ce (IV) to Ce (III). Being coated with negatively-charged hyaluronic acid, the Au/CeO2@HA facilitates accumulation in inflamed colon tissues via oral administration, reduces pro-inflammatory cytokines, and effectively alleviates colon injury in colitis mice. Overall, the Au/CeO2@HA with good biocompatibility is a promising nano-therapeutic for treating IBD. [Display omitted] •Gold core and cerium oxide shell nanoparticles (Au/CeO2) are prepared as antioxidant nanozymes.•Au/CeO2 exhibits significantly higher enzymatic catalytic activities compared with commercial ceria.•Au/CeO2@HA specifically accumulates in the inflamed colon tissues and alleviates colon injury in colitis mice.